Photophysical Studies on Drug Conjugates of Stavudine/Zidovudine and 1,8-Naphthalimide in Different Solvent Systems - Singh, Nidhi; Naaz, Farha; Verma, Rajesh; Singh, Shivendra; K. Singh, Ramendra (Asian Journal of Chemistry, 2021)
A number of fluorescent conjugates of popular anti-HIV drugs 2′,3′-didehydro-2′,3′-dideoxythymidine (stavudine, d4T) and 3′-azido-3′-deoxythymidine (zidovudine, AZT) with 1,8-naphthalimide were synthesized using the coupling reagent dicyclohexylcarbodiimide (DCC) in the presence of 4-dimethylaminopyridine (DMAP) and N,N-dimethylformamide (DMF) as solvent at room temperature. The steady-state fluorescence measurement studies on these conjugates showed solvatochromic effect. Further, the fluorescence of drug conjugates was recorded in the presence of ions like Na+ and K+ at body level concentration of 135-145 mmol L-1 and 3.6-5.1 mmol L-1, respectively, in phosphate buffer at pH 7.4 in aqueous media. It was observed that the drug conjugates did not show appreciable fluorescence quenching in presence of ions and buffer.